The presentation of the Encyclical "Veritatis Splendor" - Ratzinger, Joseph (Medicina e Morale, 1993)
This article aims to provide some possible co-ordinates for an approach to John Paul ll's latest Encyclical "Veritatis Splendor". The author, the Prefect of the Congregation for the Doctrine of the Faith, first points out two fundamental reasons why the Encyclical is necessary: on one hand because Cristianity is not pure theory, but a concrete practice, and on the other hand because morals are a question of survival for humanity. The article continues by illustrating the structure and the contents of the papal document.